EUROCOURSE lessons learned from and for population-based cancer registries in Europe and their programme owners: Improving performance by research programming for public health and clinical evaluation. Issue 9 (June 2015) - Coebergh, Jan Willem; van den Hurk, Corina; Rosso, Stefano; Comber, Harry; Storm, Hans; Zanetti, Roberto; Sacchetto, Lidia; Janssen-Heijnen, Maryska; Thong, Melissa; Siesling, Sabine; van den Eijnden-van Raaij, Janny
Abstract Population-based cancer registries (CRs) in Europe have played a supportive, sometimes guiding, role in describing geographic variation of cancer epidemics and comparisons of oncological practice and preventive interventions since the 1950s for all types of cancer, separate and simultaneously. This paper deals with historical and longitudinal developments of the roughly 160 CRs and their programme owners (POs) that emerged since 1927 and accelerating since the late 70s especially in southern and continental Europe. About 40 million newly diagnosed patients were recorded since the 1950s out of a total of 100 million of whom almost 20 million are still alive and about 10% annually dying from cancer. The perception of unity in diversity and suboptimal comparability in performance and governance of CRs was confirmed in the EUROCOURSE (EUROpe against cancer: Optimisation of the Use of Registries for Scientific Excellence in research) European Research Area (ERA)-net coordination FP7 project of the European Commission (EU) which explored best practices, bottlenecks and future challenges of CRs. Regional oncologic and public health changes but also academic embedding of CRs varied considerably, although Anno 2012 optimal cancer surveillance indeed demanded intensive collaboration with professional and institutional stakeholders in two major areas (public health and clinical research) and five minor overlapping cancer research domains: aetiologic research, mass screening evaluation, quality of care, translational prognostics and survivorship. Each of these domains address specific study questions, mixes of disciplines, methodologies, additional data-sources and funding mechanisms. POs tended to become more and more public health institutes, Health ministries, but also comprehensive cancer centres and cancer societies through more and more funding at project or programme basis. POs were not easy to pin down because of their multiple, sometimes competitive (funding) obligations and increasing complexity of cancer surveillance. But they also rather seemed to need guiding principles for Governance of 'their' CR(s) as well as to appreciate value of collaborative research in Europe and shield CRs against unreasonable data protection in case of linkages. Despite access to specialised care related shortcomings, especially of survival cohort studies, European databases for studies of incidence and survival (such as ACCIS and EUREG on the one hand and EUROCARE and RARECARE on the other hand) have proved to be powerful means for comparative national or regional cancer surveillance. Pooling of comparable data will exhibit much instructive variation in time and place. If POs of CRs would consider multinational European studies of risk and prognosis of cancer more to serve their own regional or national interest, then progress in this field will accelerate and lead to more consistent funding from the EU. The current 20 million cancer survivors and their care providers are likely to appreciate more feedback. Conclusion Most CRs remain uniquely able to report on progress against cancer by studies of variation in incidence (in time and place), detection and survival, referral and treatment patterns and their (side) effects in unselected patients, the latter especially in the (very) elderly. Programming and profiling its multiple and diverse clinical and prevention research is likely to promote involvement of public health and clinical stakeholders with a population-based research interest, increasingly patient groups and licensed 'buyers' of oncologic services.